2020
DOI: 10.1021/acs.jpcc.0c02796
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Dissociation and Electron Transfer at a Well-Defined Organic Interface of an Epitaxial C60 Layer on a Pentacene Single Crystal

Abstract: The electron transfer of a well-defined singlecrystalline organic P−N interface of the epitaxial layer of C 60 on the surface of a single-crystalline pentacene (Pen-SC) was observed using time-resolved photoemission electron microscopy (TR-PEEM) with an optical pump and probe mode. The fine energytuning of the probe light and the selected-area detection of the photoelectrons, in addition to the PEEM detection of photoelectrons, allowed the measurement of the dynamics of electrons of rather insulating organic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…34(c)] also represented an absence of strong electronic coupling between C 60 and the pentacene molecules in the ''head-on'' orientation. It is noteworthy that the ultrafast electron transfer across this well-defined molecular heterojunction was demonstrated by time-resolved photoemission electron microscopy in a very recent work, 253 which suggests potential advantage of the heteroepitaxial molecular junctions for use of photovoltaic devices with efficient exciton dissociation.…”
Section: Resultsmentioning
confidence: 86%
“…34(c)] also represented an absence of strong electronic coupling between C 60 and the pentacene molecules in the ''head-on'' orientation. It is noteworthy that the ultrafast electron transfer across this well-defined molecular heterojunction was demonstrated by time-resolved photoemission electron microscopy in a very recent work, 253 which suggests potential advantage of the heteroepitaxial molecular junctions for use of photovoltaic devices with efficient exciton dissociation.…”
Section: Resultsmentioning
confidence: 86%
“…In this photoelectron yield spectrum, it is known that, below the onset energy of the photoelectron signal from the HOMO, the small “photoelectron onset from the LUMO” can be observed via a multiple excitation process within one pulse, which is quite useful for determining E A . [ 37 ] In Figure a, the photon energy dependence of the photoelectron yields of the 4CzIPN film is marked by blue dots. The laser pulse repetition rate was set to 10 kHz, and the photon energy was swept from ≈3.3 to 3.7 eV.…”
Section: Resultsmentioning
confidence: 99%
“…This results in photoelectron measurements with a large signal-to-noise (S/N) ratio even for insulating organic films, where photoelectron spectroscopy is usually quite difficult. [37][38][39] We previously showed that TR-PEEM could indeed be used to investigate the ultrafast dynamics of excitons, including their dissociation process at an organic heterointerface for photovoltaic applications. [37] However, there are no reports on the application of the TR-PEEM method to unveil the exciton dynamics during spin-flip events, i.e., TADF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant charge carrier mobility of 35 cm 2 V −1 s −1 at room temperature has been reported by space-charge-limited current measurements [ 1 ], and intermolecular electronic band dispersion was confirmed by angle-resolved photoelectron spectroscopy for the pentacene single crystals (PnSCs) [ 2 , 3 ]. In addition, pentacene is known to exhibit singlet exciton fission efficiently, which makes this molecule quite promising for application as an organic solar cell material [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%